2016
DOI: 10.1111/imm.12680
|View full text |Cite|
|
Sign up to set email alerts
|

Decline of miR‐124 in myeloid cells promotes regulatory T‐cell development in hepatitis C virus infection

Abstract: Myeloid-derived suppressor cells (MDSCs) and microRNAs (miRNAs) contribute to attenuating immune responses during chronic viral infection; however, the precise mechanisms underlying their suppressive activities remain incompletely understood. We have recently shown marked expansion of MDSCs that promote regulatory T (Treg) cell development in patients with chronic hepatitis C virus (HCV) infection. Here we further investigated whether the HCV-induced expansion of MDSCs and Treg cells is regulated by an miRNA-m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
40
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(45 citation statements)
references
References 46 publications
(60 reference statements)
5
40
0
Order By: Relevance
“…During HCV infection, expression of several miRNAs was altered in CD33 + myeloid cells, including miR-124, which was downregulated, in part, due to HCV-induced overexpression of STAT-3 (127). Downregulation of miR-124 correlated with increased levels of IL-10 and TGF-b expression by MDSCs (127).…”
Section: Factors Involved In Mdsc Expansionmentioning
confidence: 99%
“…During HCV infection, expression of several miRNAs was altered in CD33 + myeloid cells, including miR-124, which was downregulated, in part, due to HCV-induced overexpression of STAT-3 (127). Downregulation of miR-124 correlated with increased levels of IL-10 and TGF-b expression by MDSCs (127).…”
Section: Factors Involved In Mdsc Expansionmentioning
confidence: 99%
“…Our data showed that MDSC has a positive correlation with miR-122 and 29 in control but has a negative correlation in patients. MiR-29 was significantly decreased in CD33 + myeloid cells from HCV-infected patients compared with healthy participants, revealing a decline in miR-29 expression in myeloid cells in the setting of chronic HCV infection lead to inhibition STAT-3 (Ren et al, 2016).…”
Section: Discussionmentioning
confidence: 94%
“…MDSCs and miRNAs contribute to attenuating immune responses during chronic viral infection; however, the precise mechanisms underlying their suppressive activities remain incompletely understood (Ren et al, 2016). MicroRNAs represent an interesting field of investigation with regards HCV infection and replication.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, in human immunodeficiency virus (HIV) infection, miR‐155, and miR‐29 were shown to exhibit anti‐HIV‐1 effects by modulating T cell immunity. During hepatitis C virus (HCV) infection in myeloid cells, miR‐124 was shown to be downregulated, which promotes Treg cell development by targeting STAT3; miR‐155 was also shown to be downregulated in NK cells during HCV infections, prompting an increase in IFN‐γ production by regulating Tim‐3 . miR‐17–92 are also considered essential factors in both Th1 and T FH for an effective response against viral infections .…”
Section: Mirnas Regulate T Cell Immunity During Pathogen Infectionmentioning
confidence: 99%